The 100 Most Cited Papers in the History of the American Surgical Association. Issue 4 (April 2020) - Landreneau, Joshua P.; Weaver, Matthew; Delaney, Conor P.; Aminian, Ali; Dimick, Justin B.; Lillemoe, Keith D.; Schauer, Philip R.
Abstract : Objective: The aim of this study was to determine characteristics of the most cited publications in the history of the American Surgical Association (ASA). Summary Background Data: The Annals of Surgery has served as the journal of record for the ASA since 1928, with a special issue each year dedicated to papers presented before the ASA Annual Meeting. Methods: The top 100 most cited ASA publications in the Annals of Surgery were identified from the Scopus database and evaluated for key characteristics. Results: The 100 most cited papers from the ASA were published between 1955 and 2010 with an average of 609 citations (range: 333–2304) and are included among the 322 most cited papers in the Annals of Surgery . The most common subjects of study included clinical cancer (n = 43), gastrointestinal (n = 13), cardiothoracic/vascular (n = 9), and transplant (n = 9). Ninety-three institutions were included lead by Johns Hopkins University (n = 9), University of Pittsburgh (n = 8), Memorial Sloan-Kettering (n = 7), John Wayne Cancer Institute (n = 7), University of Texas (n = 7), and 5 each from Brigham and Women's Hospital, Mayo Clinic, and University of Chicago. The majority of manuscripts came from the United States (n = 85), followed by Canada (n = 7), Germany (n = 5), and Italy (n = 5). Study design included randomized controlled trials (n = 19), retrospective matched cohort studies (n = 11), retrospective nonmatched studies (n = 46), and other (n = 24). Conclusions: The top 100 most cited publications from the ASA are highly impactful, landmark studies representing a diverse array of subject matter, investigators, study design, institutions, and countries. These influential publications have immensely advanced surgical science over the decades and should serve as inspiration for all surgeons and surgical investigators.